USING FOLKLORE TO IMPROVE STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT : THE CASE STUDY OF ELEVENTH GRADE STUDENTS OF SMA N 3 BREBES IN ACADEMIC YEAR 2021/2022 - Imtiyaz Azzahra Ramadani; Suwandi Suwandi; Siti Lestari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas PGRI Semarang, 2023)
The researcher finds out several objectives in this research there are (1) To know students’ extent of writing ability in teaching by using folklore. (2) To know students’ extent of writing ability in taught without using folklore. (3) To find out whether there are any significant differences in students’ writing ability taught with and without using folklore. (4) To find out students’ perceptions in the experiment class who were taught by using folklore. The type of this research is quantitative. The population of this research is the eleventh grade of SMA N 3 Brebes and the samples of this research are XI IPA 4 as Control class and XI IPA 5 as Experiment class. These research instruments are a test for the control class and the experiment class and an interview for the experiment class. The test consists of pre-test and post-test. The result of the research described into (1) In the control class, the mean of pre-test was 57,36, which categorized in “Equal” grade because of the score in the midst of 40,00-59,00. While, the result of the post-test was 73,75, which was categorized as a “Good” grade because the score was in the midst of 60,00-79,00. (2) In the experiment class, the mean result pre-test was 64,02 it was categorized in “Good” because the score in the midst of 60,00-79,00 and the mean result of post-test was 84, and it was classified in “Excellent” because of the score in the midst of 80,00-100,00. Therefore, it can be concluded that the score taught using folklore were higher than those taught without using folklore.